Neglected Dimensions of Success: A PRISMA Systematic Review of Non-Technical Critical Success Factors in IIS Implementation - Dini Idzni Izatri; Mudjahidin Mudjahidin (Journal of Information System Research (JOSH), 2025)
The success of Integrated Information Systems (IIS) implementation largely depends on the identification and application of Critical Success Factors (CSFs). While numerous studies have addressed CSFs, existing literature often overlooks contextual and non-technical dimensions such as cultural and environmental factors. This study presents a systematic literature review (SLR) guided by the PRISMA protocol to identify the most frequently discussed CSFs and uncover underexplored factors in IIS implementation. A total of 148 articles were retrieved from five major academic databases, with 30 meeting the inclusion criteria after a rigorous screening process. Thematic analysis revealed that top management support, project management, change management, and system quality are the most frequently cited CSFs. A simple bibliometric analysis reveals a significant research disparity: 80% of studies (24 out of 30) focus on technical-managerial factors, while a mere 20% (6 out of 30) address non-technical dimensions like organizational culture and external regulations. Furthermore, the higher education sector is critically underrepresented, accounting for only 6.7% (2 out of 30) of the reviewed literature, despite its unique complexities. This study’s primary contribution is the empirical confirmation of this "non-technical gap." Practically, these findings serve as a critical alert for university leaders and project managers, recommending a strategic shift from purely technical oversight to allocating dedicated resources for managing cultural resistance and engaging academic stakeholders throughout the implementation lifecycle to ensure sustainable success.